Physical,Chemical and Nutritional Evaluation of Shmari fruits grown in EL-Gebel Al-Akhdar. - Al-Ferjani, Salem Omar; Salem, Mohamed Shehat (Al-Mukhtar Journal of Sciences, 1995)
Since there is no available data regarding the economic value for shmari fruits ( Arbutus pavarii ) which extensively grown in El - Gebel Al-khdar as a natural flora the physical chemical and nutritional charactaristics was investigated to help evaluate their potentiality for fresh consumption and / or industrial purposes. Estimated physical properties were maturity time , color ( skin and pulp ), stone cells , fruit shape , flavor, taste and edible portion percentage; whereas the contents of total , soluble and insluble solids , acidity (as malic ), pH, total sugar , sugar : acid ratio , protien , oil , total minerals, crude fibers , pectin and total tannins were determined as a chemical components. The evaluation of nutritive value was conducted throughout caloric value , mineral contents (Na, K , Ca, Mg, Fe, Cu, P, S, and Cl) and existing vitamins such as carotene and vitamin A, detection of vitamin D , thiamin , riboflavin niacin pantothenic acid and vitamin C. As the English name implies shmari is a strawberry tree, accordingly, the above mentioned analysis was also carried out simultaneously on straw berry fruits (frogoria grandiflora), locally named "Farawla" The results were presented in comparison forms. The results indicate that shmari and strawberry fruits have relatively the same physical charac . teristics but the first have globular ( globose) shapes and the later exhibit pyriform shapes . Shmari fruits contain higer total solids , total sugars, sugar : acid ratio , fiber , pectin and total tannins and lower acidity when compared to strawberry fruits. As for nutritive value , shmari fruits contain reasonable amounts of Ca, Fe, P and higher values of K, Mg, Cu and S than those found in strawberry fruits. Shmari fruits show much better content of vitamin A when compared with strawberry fruits due to its higher content of carotenoides and also have slightly higher content of thiamin , riboflavin and vitamin C, but little lower content of pantothenic acid than strawberry fruits.